The Impact of Cognitive Knowledge on Laboratory Skills Development in Chemistry Students: A Correlational Study - Sumiati Side; Munawwarah Munawwarah; Zulqifli Alqadri (Jurnal Penelitian Pendidikan IPA, 2024)
The aim of this study is to examine the relationship between students' cognitive abilities and their laboratory skills. The research was conducted using a quantitative approach with a correlational study design. The subjects of the study were 32 students from the Chemistry Education program. The laboratory skills assessed were related to activities in the Basic Chemistry laboratory, as this course integrates both classroom learning and laboratory practice. Cognitive ability data were obtained from quizzes, midterm exams, and final exams, while laboratory skills data were collected from assessments of pre-laboratory activities (assistance and response), laboratory experiment performance, practical reports, and a final exam conducted after all practical units were completed. The data analysis revealed a strong positive correlation between cognitive abilities and laboratory skills, with a correlation coefficient of 0.65.